KARAKTERISTIK PERUSAHAAN DALAM PRAKTIK PENGUNGKAPAN WAJIB PADA LAPORAN KEUANGAN PERBANKAN SYARIAH DI INDONESIA - Arfan Amrin (Jurnal Bisnis dan Kewirausahaan, 2018)
The purpose of this research is to know the influence corporate characteristics to mandatory disclosure in annual report. The independent variables in this research are liquidity (FDR), profitability (OER), and company size (SIZE). Sampling method that used is purposive sampling and there are 31 banks that will be research objects that listed in Bank Indonesia in 2011 accord an cewithestablished criteria. Statistical analysis is the multiple linea rregression analysis used totest the data includethe t testand F test.t testused to test the partia linfluence of independent variables to dependent variable and F tes tused to test the influence of independent variables to dependent variable simultaneously. The result of this research shows that partially, independent variable liquidity (FDR) and profitability (OER) not significantly influence to Mandatory Disclosure whereas company size (SIZE) significantly influence to Mandatory Disclosure. F test results shows that the independent variables liquidity (FDR), profitability (OER), and company size (SIZE) significantly influence to mandatory disclosure. This result indicated in the significant value of F value (8.793) > F (3.34) and the significance of this research his smaller than 0.05(0.000 <0,05). The coefficient of determination indicated from Adjusted R2 that showed the number of 0,438or43.8% which means that the independent variables areliquidity (FDR), profitability (OER), and company size (SIZE) just able contribute by 43.8% to mandatory disclosure and the rest of 56.2 influence dorexplained by the other factors that are not included or are not investigated in this research.